The influence of evolution of the environment on export in family firms - Lirios Alos-Simo; Verdu-Jover Antonio-Jose; José María Gómez-Gras (European Research on Management and Business Economics (ERMBE), 2023)
The purpose of this article is to analyze the evolution of the domestic market-recessive, stable, and expansive-on export volume in family firms. Although globalization has hastened family firms toward internationalization, little is known of the influence of market evolution on export strategies. We propose a theoretical model that evaluates the influence of domestic market evolution on the percentage of export sales and the mediating role of innovation in this relationship. This model views innovation as a process that may impact export propensity when influenced by the market situation. We perform a study with panel data for a five-year period (2012-2016) from 788 family firms to identify family firms' behavior in export volume and innovation under different market conditions. The results reveal that family firms have significant results for export sales under recessive and expansive market situations. They are less prone, however, to export when markets are stable. Contrary to the predictions of the literature, our results indicate that innovation has little relevance to export volume in any of the market situations analyzed.
Keywords: M1; O31; 650; Family firm; Export; Recessive and expansive markets; Process and product innovation